2020
DOI: 10.1063/5.0022554
|View full text |Cite
|
Sign up to set email alerts
|

Effects of post-laser irradiation on the optical and structure properties of Al2O3 nanoparticles produced by laser ablation

Abstract: Alumina nanoparticles with different average particle sizes were synthesized by pulsed laser ablation of Al plates in ethanol, followed by laser irradiation at different times. Their optical and structural properties were investigated by different techniques. The experimental work showed that as the time of post-laser irradiation increased, the average particles’ size of alumina decreased. The decrease in the particle size is detected by using x-ray diffraction (XRD) technique and UV-visible absorption spectro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(13 citation statements)
references
References 45 publications
0
12
0
1
Order By: Relevance
“…Some recent studies reported the synthesis of CuONPs and Al 2 O 3 NPs by various techniques, including pyrolysis, sol-gel, sputtering, laser ablation and electrochemical reduction [23][24][25][26][27][28][29][30][31][32]. Sodeifian and Behnood [33] reported a microwave-assisted method for the synthesis of CuO/Al 2 O 3 nanocomposite for photocatalytic degradation of methylene blue removal from aqueous solution under UV irradiation.…”
Section: Introductionmentioning
confidence: 99%
“…Some recent studies reported the synthesis of CuONPs and Al 2 O 3 NPs by various techniques, including pyrolysis, sol-gel, sputtering, laser ablation and electrochemical reduction [23][24][25][26][27][28][29][30][31][32]. Sodeifian and Behnood [33] reported a microwave-assisted method for the synthesis of CuO/Al 2 O 3 nanocomposite for photocatalytic degradation of methylene blue removal from aqueous solution under UV irradiation.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 3 exhibits the histograms of the anti-bacterial activity against two gram-negative E. coli and K. pneumoniae pathogens which were induced by carbon nanotubes at 400 μg ml −1 concentration and composite multi-walled carbon nanotubes doped with iron oxide NPs at three different concentrations ratios (20, 38, 42%). Figure 5 shows the inhibition zone (IZ) image of carbon nanotubes of 400 μg ml −1 which represented as control without adding iron oxide nanoparticles, and composite carbon and iron oxide NPs in three concentrations that maintained above according to [ 8 , 9 , 20 , 21 ].
Fig.
…”
Section: Discussionmentioning
confidence: 99%
“…Figure 3 exhibits the histograms of the anti-bacterial activity against two gram-negative E. coli and K. pneumoniae pathogens which were induced by carbon nanotubes at 400 μg ml −1 concentration and composite multi-walled carbon nanotubes doped with iron oxide NPs at three different concentrations ratios (20, 38, 42%). Figure 5 shows the inhibition zone (IZ) image of carbon nanotubes of 400 μg ml −1 which represented as control without adding iron oxide nanoparticles, and composite carbon and iron oxide NPs in three concentrations that maintained above according to [8,9,20,21]. Figures 5 and 6 demonstrate the histograms and inhibition zone (IZ) image, respectively, of the anti-bacterial growth in media against gram-positive Streptococcus pyogens (S. pyogenes) and Staphylococcus aureus (S. aureus) pathogens which were induced by carbon nanotubes at 400 μg ml −1 concentration and composite carbon nanotubes doped with iron oxide NPs at three different concentrations ratios (20, 38, 42%) that goes with [4,8,9,14,15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, A. Mostafa et al showed the capability for preparing different metal oxides embedded in PVA structure in just a one-pot method by ablating metal plates (Al, Cd, and Cu) in PVA solution [ 40 ]. Moreover, A. Mostafa et al showed another facility laser parameter to enhance the PLAL method, by making laser irradiation after the laser ablation process to decrease the particle size of the prepared Al 2 O 3 NPs [ 41 ]. Furthermore, the previous contributions of Al 2 O 3 -PVA nanocomposite for the removal of heavy metals or degraded organic pollutants can be summarized in Table 1 .…”
Section: Introductionmentioning
confidence: 99%